The clinical evaluation of the new indirect calorimeter developed by the ICALIC project. Issue 10 (October 2020) - Oshima, Taku; Delsoglio, Marta; Dupertuis, Yves M.; Singer, Pierre; De Waele, Elisabeth; Veraar, Cecilia; Heidegger, Claudia-Paula; Wernermann, Jan; Wischmeyer, Paul E.; Berger, Mette M.; Pichard, Claude
Summary: Background & aims: The ICALIC project was initiated for developing an accurate, reliable and user friendly indirect calorimeter (IC) and aimed at evaluating its ease of use and the feasibility of the EE measurements in intensive care unit (ICU). Methods: This was a prospective unblinded, observational, multi-center study. Simultaneous IC measurements in mechanically ventilated ICU patients were performed using the new IC (Q-NRG®) and currently used devices. Time required to obtain EE was recorded to evaluate the ease of use of Q-NRG® versus currently used ICs and EE measurements were compared. Conventional descriptive statistics were used: data as mean ± SD. Results: Six centers out of nine completed the required number of patients for the primary analysis. Mean differences in the time needed by Q-NRG® against currently used ICs were −32.3 ± 2.5 min in Geneva (vs. Deltatrac®; p < 0.01),  −32.3 ± 3.1 in Lausanne (vs. Quark RMR®; p < 0.05),  −33.7 ± 1.4 in Brussels (vs. V-Max Encore®; p < 0.05),  −26.4 ± 7.8 in Tel Aviv (vs. Deltatrac®; p < 0.05),  −28.5 ± 3.5 in Vienna (vs. Deltatrac®; p < 0.05), and 0.3 ± 1.2 in Chiba (vs. E-COVX®; p = 0.17). EE (kcal/day) measurements by the Q-NRG® were similar to the Deltatrac® in Geneva and Vienna (mean differences ± SD: −63.1 ± 157.8 (p = 0.462) and −22.9 ± 328.2 (=0.650)), but significantly different in Tel Aviv (307.4 ± 324.5, p < 0.001). Significant differences were observed in Lausanne (Quark RMR® :  −224.4 ± 514.9, p = 0.038) and in Brussels (V-max®: −449.6 ± 667.4, p < 0.001), but none was found in Chiba (E-COVX®; 55.0 ± 204.1, p = 0.165). Conclusion: The Q-NRG® required a much shorter time than most other ICs to determine EE in mechanically ventilated ICU patients. The Q-NRG® is the only commercially available IC tested against mass spectrometry to ensure gas accuracy, while being very easy-to use.